mRNA decapping enzyme2 DCP2 expression correlates with progression and prognosis of hepatocellular carcinoma - Tianyi Huang; Rui Wang; Cuihua Lu; Jiaying Zhang (Scientific Reports)
Abstract mRNA decapping enzyme 2 (DCP2) is a key regulator of mRNA degradation, influencing RNA metabolism and gene expression. While implicated in various diseases, its role in Hepatocellular carcinoma (HCC) remains unclear. This study explores DCP2 as a potential biomarker for HCC through bioinformatics and experimental analyses. Public databases, including The Cancer Genome Atlas (TCGA) and GEPIA2 online database, revealed significant DCP2 upregulation in HCC tissues, correlating with Tumor-Node-Metastasis (TNM) staging, histological grading, platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and alpha-fetoprotein (AFP) levels. Prognostic analysis confirmed high DCP2 expression as an indicator of poor overall survival (OS). Functional enrichment analyses linked DCP2 to cancer-associated pathways, including PI3K/Akt, Hippo signaling, cholesterol metabolism, and oxidative phosphorylation. Immune infiltration analysis showed significant correlations with tumor-associated macrophages (TAMs) and regulatory T cells (Tregs), suggesting a role in immune modulation. Experimental validation via western blot and immunohistochemistry (IHC) confirmed elevated DCP2 expression in HCC cell lines and tissues. These findings suggest that DCP2 may be involved in HCC progression by influencing mRNA degradation, cancer-related signaling, and the immune microenvironment. Although DCP2 shows potential as a diagnostic and prognostic biomarker, as well as a therapeutic target, further functional studies—such as gene knockdown and overexpression experiments—are needed to confirm its mechanistic role in the development of hepatocellular carcinoma (HCC).